2013
DOI: 10.1089/scd.2013.0023
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Mesenchymal Stem Cell Therapy for Patients with Active Rheumatoid Arthritis: Safety and Efficacy

Abstract: This study was designed to assess the safety and efficacy of human umbilical cord mesenchymal stem cells (UC-MSCs) in the treatment of rheumatoid arthritis (RA). In this ongoing cohort, 172 patients with active RA who had inadequate responses to traditional medication were enrolled. Patients were divided into two groups for different treatment: disease-modifying anti-rheumatic drugs (DMARDs) plus medium without UC-MSCs, or DMARDs plus UC-MSCs group (4×10(7) cells per time) via intravenous injection. Adverse ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
181
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(204 citation statements)
references
References 40 publications
8
181
1
1
Order By: Relevance
“…In refractory RA patients, MSC therapy induced a short-term reduction in clinical scores, but the clinical improvement was not maintained during the follow-up period; thus, complete remission was not achieved in any patient [35]. In a larger study, MSC therapy provided clinical efficacy in active RA patients for at least 3 months, and additional MSC administrations at 3 months stabilized the disease [36]. Furthermore, in a recent study of MSC therapy in ALS patients, it was demonstrated that immunomodulatory factors secreted by MSCs were predictive of the effectiveness of MSC therapy and could potentially identify the patients responsive to therapy.…”
Section: Limitations Of Msc-mediated Immune Modulation In the Clinicamentioning
confidence: 95%
“…In refractory RA patients, MSC therapy induced a short-term reduction in clinical scores, but the clinical improvement was not maintained during the follow-up period; thus, complete remission was not achieved in any patient [35]. In a larger study, MSC therapy provided clinical efficacy in active RA patients for at least 3 months, and additional MSC administrations at 3 months stabilized the disease [36]. Furthermore, in a recent study of MSC therapy in ALS patients, it was demonstrated that immunomodulatory factors secreted by MSCs were predictive of the effectiveness of MSC therapy and could potentially identify the patients responsive to therapy.…”
Section: Limitations Of Msc-mediated Immune Modulation In the Clinicamentioning
confidence: 95%
“…In a previous study, we demonstrated that the level of Treg cells increased after UC-MSC treatment in active RA patients. 12 Based on those results, we proposed the novel hypothesis that the efficacy of MSCs in the treatment of autoimmune diseases could be mediated by Treg function in the restoration of the thymic dysfunction in those patients.…”
Section: Discussionmentioning
confidence: 97%
“…11 Furthermore, umbilical cord derivedMSCs (UC-MSCs) can also increase the percentage of regulatory T cells (Treg cells) in the peripheral blood of treated patients with rheumatoid arthritis. 12 Because Treg cells are primarily generated in the thymus, we hypothesized that the therapeutic efficacy of MSCs could be mediated by regulating thymic function in patients with those diseases. Compared to other sources, UC-MSCs have well-documented self-renewal and multipotent differentiation properties and possess immunoregulatory capacities.…”
Section: Introductionmentioning
confidence: 99%
“…One Phase I/ II trial in a cohort of 172 patients with active RA has been completed, showing that treatment with both umbilical cord MSC (UC-MSC) and DMARDs significantly improved the 28-joint DAS for 3-6 mo compared with DMARD treatment alone. 187 These beneficial effects were associated with an increase in peripheral blood Tregs and a decrease in serum TNF and IL-6. It is encouraging that this first MSC trial in RA patients indicates that MSC treatment may provide clinical benefit, but further, larger, (Phase III) trials are required to obtain robust data on their safety and efficacy.…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%